Introducing the National Library of Poland Descriptors to the Polish National Bibliography. Issue 1 (2nd January 2019) - Cieloch-Niewiadomska, Joanna
Abstract: The paper presents the new verbal indexing language (National Library of Poland Descriptors) used in Polish national bibliography. History and organization of Polish national bibliography as well as the context of other changes in the National Library of Poland are described. The paper provides information about National Library of Poland Descriptors main principles, and describes the steps that have been undertaken by subject specialists to improve the subject description of the national bibliography records, especially of its online version. The result of these changes is compared with recommendations for subject access in national bibliographies proposed by IFLA.